DOI: 10.14393/ufu.di.2014.109
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento profissional do médico professor: um estudo de caso na Universidade Federal de Uberlândia

Abstract: pela postura acadêmica firme, ética e enriquecedora dos meus conhecimentos científicos e pedagógicos, pelo estímulo confiante em minha capacidade e, sobretudo, pela amizade construída ao longo desses dois anos. À Profª Drª Silvana Malusá, pelas colocações tão pertinentes feitas ao texto de qualificação, pelas contribuições, pelas "dicas" ao sucesso de meu trabalho e por selarmos uma amizade tão importante durante minha caminhada na Pós-Graduação.À Profª Drª Elenita Pinheiro de Queiroz Silva, pelas importantes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In another study by Silva et al (1999) the author applied the control chart in a dairy industry, the process steps chosen for the investigation of the quality level were pasteurization, skimming of milk and packing, the author collected samples of the steps studied for two months and analyzed the temperature of the milk, percentage of fat and the weight of the final product, it was observed that there was failure in all stages of the production process, concluding that production is completely out of control; The author states that dairy has fragility in the quality assurance of products and recommends new financial investments in the company.…”
Section: Resultsmentioning
confidence: 92%
“…In another study by Silva et al (1999) the author applied the control chart in a dairy industry, the process steps chosen for the investigation of the quality level were pasteurization, skimming of milk and packing, the author collected samples of the steps studied for two months and analyzed the temperature of the milk, percentage of fat and the weight of the final product, it was observed that there was failure in all stages of the production process, concluding that production is completely out of control; The author states that dairy has fragility in the quality assurance of products and recommends new financial investments in the company.…”
Section: Resultsmentioning
confidence: 92%
“…was used for the five employees of Digital Company, designed and adapted from the studies developed by Junior (2020), Mendes (2020), andSilva (2021). The questionnaire intended for the employees of Digital Company contains 7 closed questions aimed at addressing these professionals' perceptions regarding productivity, quality, improvements in the profession, and motivation resulting from the implementation of digitization in accounting.…”
Section: 3sample Collection Methodsmentioning
confidence: 99%
“…This phenomenon seems to be linked to the persistently traditional and outdated image attributed to the profession. In Portugal, according to Silva (2021), although the COVID-19 pandemic was a challenging period, it presented an opportunity to promote change and adaptation to digital accounting, significantly improving automations, with the Portuguese state contributing positively by automating and simplifying some tax declarations and the exchange of information between various public institutes, which helped to promote the dematerialization of the Portuguese tax system.…”
Section: 2evolution From Traditional To Collaborative Accountingmentioning
confidence: 99%
“…According to ADA, assistive technology is defined as "a wide range of equipment, services, strategies, and practices designed and applied to alleviate functional problems encountered by individuals with disabilities" [4].…”
Section: A Assistive Technologymentioning
confidence: 99%